2018
DOI: 10.31661/jbpe.v0i0.556
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Virtual Reality Technique (Cervigame®) Compared to Conventional Proprioceptive Training to Treat Neck Pain: A Randomized Controlled Trial

Abstract: Background: Despite the potential benefits of virtual reality technology in physical rehabilitation, only a few studies have evaluated the efficacy of this type of treatment in patients with neck pain.Objective: The aim of this study was to compare the effects of virtual reality training (VRT) versus conventional proprioceptive training (CPT) in patients with neck pain.Methods: Forty four participants with nonspecific chronic neck pain were randomly assigned to VRT or CPT in this assessor-blinded clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 34 publications
3
37
0
1
Order By: Relevance
“…A television or PC screen was used in the following situations (n=9): support of a group cognitive behavior therapy containing specific content for developing relaxation and mindfulness skills, as an adjunct to the activity pacing component, with education, activity management, and relapse prevention, to induce positive emotions and promote motivation, self-efficacy, and behavior activation [ 48 , 55 , 57 , 58 ]. Other authors used a television or PC screen to practice motor execution by games, such as racing cars using phantom movements and matched random target postures of a virtual arm [ 66 , 77 ], a rabbit attempting to reach carrots and avoid obstacles [ 69 ], or a target-oriented motor control task where hand exercises consisted of reaching out, grasping, transferring, and placing [ 75 ]. In another study, patients with burning mouth syndrome watched their tongues on a computer screen with illusions and performed tongue movements [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A television or PC screen was used in the following situations (n=9): support of a group cognitive behavior therapy containing specific content for developing relaxation and mindfulness skills, as an adjunct to the activity pacing component, with education, activity management, and relapse prevention, to induce positive emotions and promote motivation, self-efficacy, and behavior activation [ 48 , 55 , 57 , 58 ]. Other authors used a television or PC screen to practice motor execution by games, such as racing cars using phantom movements and matched random target postures of a virtual arm [ 66 , 77 ], a rabbit attempting to reach carrots and avoid obstacles [ 69 ], or a target-oriented motor control task where hand exercises consisted of reaching out, grasping, transferring, and placing [ 75 ]. In another study, patients with burning mouth syndrome watched their tongues on a computer screen with illusions and performed tongue movements [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychological outcomes, such as kinesiophobia and fear, mood, satisfaction, expectations of pain, pain focus, time spent thinking about pain, self-efficacy, emotions, motivation, stress, catastrophizing, acceptability, global impression of change, ownership, and agency, were measured in 19 studies [ 45 , 48 , 52 , 55 - 59 , 62 - 65 , 67 , 70 - 72 , 74 , 81 , 82 ]. Functional outcomes, including disability, physical comfort, strength, fitness, and sleep, were measured in 15 studies [ 45 , 55 - 57 , 59 , 60 , 62 , 64 , 65 , 69 - 72 , 77 , 82 ]. Functional capacity (evaluated by measuring balance, repetition index, step test, and composite value) was measured in 5 studies [ 56 , 62 , 65 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En contraste con los resultados obtenidos, en un reciente estudio de Rezai et al observó mejoras en la discapacidad en pacientes con dolor cervical tras la aplicación de RV mediante un juego controlado por el movimiento de la cabeza. Además, dicha mejora se observó después del tratamiento, y cinco semanas después del mismo (Rezaei et al, 2018). En concordancia con estos autores, Sarig et al también obtuvieron resultados favorables con la aplicación de RV en las variables discapacidad y dolor (Sarig Bahat et al, 2018).…”
Section: Los Resultados Obtenidos Se Encuentran Enunclassified
“…On the other hand, the results of this research are not supported by those found in another study that compared nonimmersive VR exercises with proprioceptive training in patients with neck pain, using eight sessions over a period of 4 weeks. That study observed that patients in the VR group improved more in terms of pain and disability than the group that performed proprioceptive exercises [ 49 ].…”
Section: Discussionmentioning
confidence: 99%